2012
DOI: 10.21273/hortsci.47.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Liverwort Control: An Ancillary Role for Ozone-based Irrigation Water Treatment Systems?

Abstract: Marchantia polymorpha L. (a thalloid liverwort) is a common plant pest in nursery and greenhouse production systems. The rapid growth and dissemination of this pest can result in heavy mats of thallus tissue on the surface of pots, which restrict water penetration, compete for nutrients, and provide a habitat for other pests and disease vectors. The sensitivity of liverwort to aqueous ozone was examined to determine if routine use of ozone, as a component of an irrigation wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Other organic products such as pelargonic acid, acetic acid products, d-limonene, and ammonium nonanoate have shown some suppression of common liverwort, but these compounds often require repeated application and can cause severe damage to ornamentals crops (Table 2). Graham and Dixon (2012) reported that the maintenance of a small residual aqueous ozone concentration during the distribution of irrigation water to the crop has the potential to offer some level of common liverwort control. They conducted experiments to evaluate contact time thresholds and application frequencies suitable for common liverwort management.…”
Section: Overview Of Chemical Control Of Common Liverwortmentioning
confidence: 99%
“…Other organic products such as pelargonic acid, acetic acid products, d-limonene, and ammonium nonanoate have shown some suppression of common liverwort, but these compounds often require repeated application and can cause severe damage to ornamentals crops (Table 2). Graham and Dixon (2012) reported that the maintenance of a small residual aqueous ozone concentration during the distribution of irrigation water to the crop has the potential to offer some level of common liverwort control. They conducted experiments to evaluate contact time thresholds and application frequencies suitable for common liverwort management.…”
Section: Overview Of Chemical Control Of Common Liverwortmentioning
confidence: 99%